Foreign language as a tool of communicative competency development of future teachers of technical disciplines - Zelenin, H. (Problems of Engineer-Pedagogical Education, 2019)
Based on the analysis psychological and pedagogical works, the article attempted to define the concept “foreign language professional competence” in the context of modern higher technological education, as a dynamic, integrative, important characters of future teachers of technical disciplines, that are enabling them to realize successful professional contacts at the resolving of technical problems and communication situations in professional activities, and consists of motive-value - based (the presence of positive attitude towards processes of intercultural professional exchange, is expressed through a willingness to keep activity of communicative professional experience, directed to solving the technical problem), cognitive (foreign language skills, as well as the understanding of sociocultural, sociolinguistic nature of a language to deal with professional communicative tasks), action (implementation of activities, which aims at intercultural professional communicative interaction in order to gain and complete communicative experience), reflexively – estimating (autonomous assessment of the achievements of communicative professional activities and improvement of obtained communicative experience) components. The author underlines core competency (linguistic, communicative, and pragmatic) that made up structurally substantive model of foreign language professional competence of future teachers of technical disciplines; highlights, that destination, substantive, procedurally technological and productive components are considered as key structural part of model for of foreign language professional competence development of technical expertise. The article specifies conditions that foster foreign language professional competence development of students in the training process of a foreign language in high technical schools. According to analysis of theoretical presentations, university practice, it also determines that process of foreign language professional competence development of technical expertise has a number of phases, following one after another; claimed that dynamics of foreign language professional competence development is realized in this sequence: from development of linguistic, communicative, and sociocultural competency towards foreign language professional competence development and then to the development phase of professionalism of additional language personality of future teachers of technical disciplines.